2019
DOI: 10.1111/1750-3841.14789
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Alkylresorcinols on Autophagy, Migration, and Invasion of HepG2 Cells

Abstract: Alkylresorcinols are phenolic lipids that mainly exist in the cortex of grains, and they exhibit anticancer activity against various cancer cells in vitro. However, the underlying action mechanisms are still unclear. In our study, the influence of alkylresorcinols C19:0 and C21:0 (ARs) upon migration, invasion, and autophagy in human hepatoblastoma HepG2 cells was evaluated. Results showed that ARs at 80 and 160 µg/mL significantly suppressed cells proliferation, migration, and invasion, downregulated the expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 32 publications
(40 reference statements)
1
5
0
Order By: Relevance
“…To verify our speculation, also considering HAP treatment had a more obvious promoting‐autophagy effect, we selected HepG2 cells in high dose of APE treatment group being treated with autophagy blockers, CQ and leupeptin, respectively. Consistent with Guo' study (Guo, Yang, & Li, 2019), elevated protein accumulations of LC3‐II and p62 were observed in CQ‐treated HepG2, and LC3‐II protein accumulation was more obvious in APE treatment group. Similar phenomena were also observed in leupeptin‐treated cells.…”
Section: Discussionsupporting
confidence: 86%
“…To verify our speculation, also considering HAP treatment had a more obvious promoting‐autophagy effect, we selected HepG2 cells in high dose of APE treatment group being treated with autophagy blockers, CQ and leupeptin, respectively. Consistent with Guo' study (Guo, Yang, & Li, 2019), elevated protein accumulations of LC3‐II and p62 were observed in CQ‐treated HepG2, and LC3‐II protein accumulation was more obvious in APE treatment group. Similar phenomena were also observed in leupeptin‐treated cells.…”
Section: Discussionsupporting
confidence: 86%
“…48,49 One study found that the knockdown of HSP90 blocked AKT1 phosphorylation. 64 However, Ars and AR-C17 treatment also decreases p-AKT in some cancer cells (HepG2 cells and MCF-7 breast cancer cells), 47,48 and whether this is related to the inhibition of HSP90 by ARs or its metabolites needs to be further verified. EP300 (E1A-associated protein p300) is a pleiotropic multidomain coactivator that acts as a histone/lysine acetyl transferase, chromatin remodeler, and acetyltransferase for nonhistone targets.…”
Section: Discussionmentioning
confidence: 99%
“…48,49 One study found that the knockdown of HSP90 blocked AKT1 phosphorylation. 64 However, Ars and AR-C17 treatment also decreases p-AKT in some cancer cells (HepG2 cells and MCF-7 breast cancer cells), 47,48 and whether this is related to the inhibition of HSP90 by ARs or its metabolites needs to be further verified.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The expression of LC3II and LC3II/LC3I also increased rapidly in gastric cancer cells treated with germacrone ( Figures 4B, C). Baf A1 is an autophagy inhibitor, which affects the binding of autophagosomes to lysosomes, and the increasing of LC3 (24,25). In our study, we used Baf A1 to investigate the regulatory target of germacrone on autophagy.…”
Section: Germacrone Promoted the Formation Of Autophagosomes In Gastrmentioning
confidence: 99%